Thoracic trauma severity contributes to differences in intensive care therapy and mortality of severely injured patients: analysis based on the TraumaRegister DGU® - Jörg Bayer (World Journal of Emergency Surgery, 2017)
Abstract Background Thoracic trauma is a relevant source of comorbidity throughout multiply-injured patient care. We aim to determine a measurable influence of chest trauma’s severity on early resuscitation, intensive care therapy, and mortality in severely injured patients. Methods Patients documented between 2002 and 2012 in the TraumaRegister DGU®, aged ≥ 16 years, injury severity score (ISS) ≥ 16 are analyzed. Isolated brain injury and severe head injury led to exclusion. Subgroups are formed using the Abbreviated Injury ScaleThorax. Results Twenty-two thousand five hundred sixty-five patients were predominantly male (74%) with mean age of 45.7 years (SD 19.3), blunt trauma (95%), mean ISS 25.6 (SD 9.6). Overall mean intubation period was 5.6 days (SD 10.7). Surviving patients were discharged from the ICU after a mean of about 5 days following extubation. Thoracic trauma severity (AISThorax ≥ 4) and fractures to the thoracic cage significantly prolonged the ventilation period. Additionally, fractures extended the ICU stay significantly. Suffering from more than one thoracic injury was associated with a mean of 1–2 days longer intubation period and longer ICU stay. Highest rates of sepsis, respiratory, and multiple organ failure occurred in patients with critical compared to lesser thoracic trauma severity. Conclusion Thoracic trauma severity in multiply-injured patients has a measurable impact on rates of respiratory and multiple organ failure, sepsis, mortality, time of mechanical ventilation, and ICU stay.